Gendered Constructions of Leadership in Danish Job Advertisements. Issue 6 (28th April 2014) - Askehave, Inger; Zethsen, Karen Korning
<x xml:space="preserve">Abstract</x> The purpose of this article is to consider the gender imbalance at top management level from a discourse analytical perspective. More specifically, it investigates the language of 39 Danish top executive job advertisements and considers which leadership identities are projected as desirable or necessary. This is done by carrying out two interlinked studies: a semantic field analysis of the sections in the job advertisements describing the leadership traits of the ideal candidate (Study 1) and a study of MBA students' responses to extracts from the advertisements as far as gender is concerned (Study 2). Semantic field analysis reveals that all the job advertisements are gender‐biased and that most traits described in the advertisements are associated with traditional or stereotypical masculine attributes. Study 2 confirms this finding, as respondents (MBA students) assign a masculine identity to the vast majority of the extracts from the job advertisements.